Enabling solar energy production for low-income communities - Sua, Lutfu S.; Balo, F. (Institution of Engineering and Technology, 2024)
Solar power has a lot of significance among renewable power resources. Electric production from solar power has become a priority for many nations around the world in the last few years. It is very important to choose the right solar panel when it comes to producing electricity through sunlight. If the selected solar panel is not suitable for the system, there may be many different disadvantages, such as waste of energy and capital. In this study, it is attempted to determine the best solar panel in terms of technical features and cost in a solar facility planned to be used to enable widespread use of solar energy for low-income communities. While determining the solar panels studied worldwide among the alternative brands, the evaluation of some characteristics of the brands for low-income communities was taken into consideration simultaneously. Such characteristics include, long "product warranty length," minimum "warranted yearly efficiency reduction," and maximum "warranted energy output," etc. For the case study, 415 W monocrystalline solar panel brands were analyzed. The results were evaluated using Analytic Hierarchy Process (AHP) among Multi-Criteria Decision Making (MCDM) techniques. © The Institution of Engineering and Technology and its licensors 2024.
Keywords: Clean energy; Green housing; Low-income communities; MCDM; Solar power